2013
DOI: 10.3389/fnins.2013.00129
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tactile, auditory, and visual modality for brain-computer interface use: a case study with a patient in the locked-in state

Abstract: This paper describes a case study with a patient in the classic locked-in state, who currently has no means of independent communication. Following a user-centered approach, we investigated event-related potentials (ERP) elicited in different modalities for use in brain-computer interface (BCI) systems. Such systems could provide her with an alternative communication channel. To investigate the most viable modality for achieving BCI based communication, classic oddball paradigms (1 rare and 1 frequent stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 60 publications
2
87
0
Order By: Relevance
“…In addition to the assessment of the system effectiveness, the types of stimulation exploited to elicit the P3 (Kaufmann et al, 2013;Townsend et al, 2010), the user's motivation (Nijboer et al, 2010), and selective attention were shown to influence the BCI performance of people with neurodegenerative diseases.…”
Section: Bcis For Communication In End-usersmentioning
confidence: 99%
“…In addition to the assessment of the system effectiveness, the types of stimulation exploited to elicit the P3 (Kaufmann et al, 2013;Townsend et al, 2010), the user's motivation (Nijboer et al, 2010), and selective attention were shown to influence the BCI performance of people with neurodegenerative diseases.…”
Section: Bcis For Communication In End-usersmentioning
confidence: 99%
“…The results in [20] indicated that the experiments achieved information transfer rates of 7.8 bit/min on average and 27 bit/min for the best subject. A very recent report [7] additionally confirmed superiority of the tactile BCI (tBCI) in comparison with visual and auditory modalities tested with a locked-in syndrome (LIS) subject [14].…”
Section: Introductionmentioning
confidence: 99%
“…While there is a large variety of control interfaces, a small number of studies have focused on their formal performance evaluation and comparison [205,206,207,208,209,210,211,212]. The performance of control interfaces is rarely evaluated consistently, which prevents an objective evaluation and comparison.…”
Section: Evaluation Of Control Interfacesmentioning
confidence: 99%